Эффективность применения эластомерных материалов для внутренних теплозащитных покрытий ракетных твердотопливных двигателей - Козис, К.В.; Потапов, А.М.; Манько, Т.А. (Вісник Українського матеріалознавчого товариства, 2016)
A possibility to improve the properties for a rubber of 1001 grade as the main material for inside thermal protective coating under exploting solid propellant rocket engine from composite materials is examined in the article. To confirm a workability of this rubber grade and to study the processes which takes place in its structure under an influence of a temperature the investigation were carried out with using derivatograph analysis. Temperature intervals and maximum temperature of the main thermal destruction of the 1001 grade rubber (the maximum temperature of the endoeffect on DTG line) were determined by using DTG and TG analyses. The temperature maximum which replies to the biggest rate of mass loss is the characteristic temperature point which gives the real information about material structure.